The provision of vitamin K to the nursing mothers - A.V. Solianik (Zaslavsky O.Yu., 2018)
Background. Newborns and young infants, who are breastfed, are prone to vitamin K deficiency. The purpose of our work was to study the provision of rations for the nursing mothers of children, who are exclusively breastfed and who are at risk of developing latent hypovitaminosis K. Materials and methods. The object of the survey was 50 healthy women aged 19 to 39 years, who are breast-feeding children aged 0-6 months. To calculate the daily intake of vitamin K, a specially developed program was used - "Vitamin K intake calculator". According to 3 typical daily diets, the average intake of vitamin K per day (μg) was calculated. Results. The average intake of vitamin K was 61.0 ± 3.5 μg. The data obtained were distributed in quartiles. The values of the lower quartile (0-25%) were 26.3-37.1 μg, of the upper (75-100%) - 85.2-99.2 μg. Seven (14 %) of the upper quartile (75-100%) representatives, who have rations close to the physiological consumption of vitamin K, are informed about the significance of this vitamin and daily use of products with its high content. Another 23 (46 %) nursing mothers, representatives of the 2nd - 3rd quartiles (25-75%), were not sufficiently informed about the significance of vitamin K, but consumed foods with its high and medium contents. Twenty (40 %) nursing mothers, representatives of the lower quartile (0-25 %), were not sufficiently informed about the value of vitamin K and did not eat foods with its high content. Conclusions. The supply of vitamin K to the rations of nursing mothers in the industrial city of southern Ukraine does not reach the recommended level of its consumption - 120 μg per day. 14 % of respondents regularly eat foods with high vitamin K content, and this can provide 75-85 % of the daily requirement for vitamin K. Insufficient supply of nursing mothers with vitamin K can exacerbate vitamin K deficiency in infants aged 0-6 months.